Development of Problem-Based Mathematics Teaching Materials for Elementary School Students - Nori Marsena; Ahmad Fauzan; Nurhizrah Gistituati (Postgraduate School, Universitas Negeri Padang, 2021)
This study aims to develop teaching materials based on Mathematics Based Problem-Based Learning in fourth-grade students of SD 183 Pekanbaru in accordance with the 2013 curriculum and to produce valid, practical, and effective teaching materials for use in learning. This research is a development study with a development model adapted from the Plomp model. The Plomp model consists of three phases covering the preliminary research phase, prototyping phase, and assessment phase. Based on the results of the analysis based on the experts, namely: material experts, linguists, and graphics experts determine greatest common divisor and Least common multiple teaching materials based on problem-based learning criteria meet the criteria with an average score of 86%. Based on the analysis of teacher with an average score of 82% and student worksheets consisting of 16 people obtained from problem-based learning based on greatest common divisor and Least common multiple teaching materials meet the requirements with an average score of 86%. Furthermore, 84% of the students could achieve the Minimum Standard Score, so that learning materials can be improved based on greatest common divisor and Least common multiple teaching materials Problem Based Learning requires valid, practical, and effective criteria and can be used in learning.